Modelagem de distorções entre sad 69 e sirgas 2000 pelo método de shepard e grades regulares - Magna Júnior, João Paulo [UNESP]; Camargo, Paulo de Oliveira [UNESP]; Galo, Maurício [UNESP] (My University, 2009)
Brazil follows the tendency of some countries to update and/or review their fundamental geodetic network. The adoption of geocentric referentials like SIRGAS 2000, the new official reference system of the Geodetic Brazilian System has been an advance. Changes in referential implies in coordinates changes on the network stations as well as the network geometry. To make use of analogical and digital products which are already known in the old referentials are necessary approaches to the coordinate conversion, which minimize the distortions between the used reference frames. This paper presents a distortion modeling approach between reference frames, based on distortion grid generation by using the Shepard's method. To analyze the approach some experiments were performed with the generation of a 1°×1° distortion grid to model the distortions between SAD 69 (1996) and SIRGAS (2000) frames. The results in the test stations were promising, with an average reduction of 50% in the RMS coordinates after the distortions modeling.
Distortion modeling between SAD 69 and SIRGAS 2000 based on Shepard method and regular grids
Keywords: Distortion modeling; Reference systems; Shepard's interpolator